Pengaruh Perputaran Persediaan Barang Jadi, Debt To Equity Ratio, dan Pertumbuhan Penjualan Terhadap Profitabilitas Perusahaan Food and Beverages yang Terdaftar Di Bursa Efek Indonesia Tahun 2010-2012 - Febi Nurindah Sari; Kirmizi Ritonga; Nur Azlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Income or profit is one of the main objectives the establishment of any business enterprise. Without profit, the company can not be a going concern. The survival of the company (going concern) is influenced by the profitability of the company itself. Profitability illustrates the company's ability to profit through all abilities. The purpose of this study was to analyze the effect of independent variables (Inventory Turnover Period, Debt to Equity Ratio, Sales Growth) on the dependent variable is Profitability (NPM). Based on the results of the discussion over the whole hypothesis testing are: 1) There is no significant Effect of Finished Goods Inventory Turnover on Net Profit Margin, 2) There is no significant Effect of Debt to Equity Ratio on Net Profit Margin. And 3) There is no significant Effect of Sales Growth on Net Profit Margin.Keywords : Finished Goods Inventory Turnover, Debt To Equity Ratio, Sales Growth and Profitability